Sosialisasi Praktik Ekonomi Manajerial dalam Penyusunan Anggaran untuk Peningkatan Kinerja Karang Taruna - Sesri Selina; Etty Zuliawati Zed; Ihsan Putra Ramadhan; Addiin Dwi Saputro; Nadia Siti Ajrak; Laela Zhafarina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The objective of the dissemination activity on managerial economic practices related to budgeting was to enhance the understanding and capacity of Karang Taruna administrators in managing organizational finances efficiently and responsibly.through training sessions and interviews, participants gained practical insights into planning, controlling, and evaluating budgets based on managerial economics principles. The outcomes of the activity demonstrated that applying efficiency and effectiveness principles in budgeting can improve accountability, transparency, and overall organizational performance.the budgeting process for the 2025 UMKM Bazaar served as a practical example, showing that structured and participatory financial management can enhance organizational governance and optimize the use of available resources.according to the final evaluation, the administrators showed significant improvement in budget planning and management skills, contributing to better performance and increased professionalism within Karang Taruna.this initiative represents a strategic step toward fostering the independence of community organizations in implementing sustainable programs.